Martin Luther( 1483-1546): sa contribution à la langue allemande et à la libération de la conscience - AGOSSAVI, ALPHONSE (My University, 2018)
This paper deals with the role of Martin Luther and the "Reformation" movement in the development of german language and the liberation of human consciousness. The main point is to describe the maising consequences of Reformation on the religious, political, social life of the German people in that century. It is a social historical point of view. I insist also on the modernity and the actuality of Martin Luther and the "Reformation".
Keywords: Réformation-Martin Luther-; Liberté religieuse-; Mentalité-; Société-; Conscience.